Loodete ja vastsündinute kaasasündinud väärarendite levimus: Eesti üleriigiline uuring aastal 2020 - Süüden, Eva-Liina; Muru, Kai; Põder, Kelli; Rull, Kristiina (Eesti Arst, 2024)
Eesti Arst 2024; 103(8):385